Herpes Simplex Virus 1 Infection of Neuronal and Non-Neuronal Cells Elicits Specific Innate Immune Responses and Immune Evasion Mechanisms - Verzosa, Amanda L.; McGeever, Lea A.; Bhark, Shun-Je; Delgado, Tracie; Salazar, Nicole; Sanchez, Erica L. (Frontiers in Immunology, 2021)
Alphaherpesviruses (α-HV) are a large family of double-stranded DNA viruses which cause many human and animal diseases. There are three human α-HVs: Herpes Simplex Viruses (HSV-1 and HSV-2) and Varicella Zoster Virus (VZV). All α-HV have evolved multiple strategies to suppress or exploit host cell innate immune signaling pathways to aid in their infections. All α-HVs initially infect epithelial cells (primary site of infection), and later spread to infect innervating sensory neurons. As with all herpesviruses, α-HVs have both a lytic (productive) and latent (dormant) stage of infection. During the lytic stage, the virus rapidly replicates in epithelial cells before it is cleared by the immune system. In contrast, latent infection in host neurons is a life-long infection. Upon infection of mucosal epithelial cells, herpesviruses immediately employ a variety of cellular mechanisms to evade host detection during active replication. Next, infectious viral progeny bud from infected cells and fuse to neuronal axonal terminals. Here, the nucleocapsid is transported via sensory neuron axons to the ganglion cell body, where latency is established until viral reactivation. This review will primarily focus on how HSV-1 induces various innate immune responses, including host cell recognition of viral constituents by pattern-recognition receptors (PRRs), induction of IFN-mediated immune responses involving toll-like receptor (TLR) signaling pathways, and cyclic GMP‐AMP synthase stimulator of interferon genes (cGAS-STING). This review focuses on these pathways along with other mechanisms including autophagy and the complement system. We will summarize and discuss recent evidence which has revealed how HSV-1 is able to manipulate and evade host antiviral innate immune responses both in neuronal (sensory neurons of the trigeminal ganglia) and non-neuronal (epithelial) cells. Understanding the innate immune response mechanisms triggered by HSV-1 infection, and the mechanisms of innate immune evasion, will impact the development of future therapeutic treatments.